2023
DOI: 10.35848/1347-4065/acba24
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductive nanoparticles coated with polymeric ionic liquids via RAFT polymerization with particles method for low-humidity proton conduction

Abstract: Proton conduction in the current polymer electrolyte membrane depends on water molecules, which necessitates high-humidity environments. On the contrary, proton conduction in low-humidity environments has been required for expanding operation conditions of polymer electrolyte fuel cells. Recently, ionic liquids (ILs) have been focused on novel proton conductive materials, however, the ILs were hard to fabricate the self-standing membrane owing to their fluidity. In this paper, we have developed composite mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Since the propyl group in 1PIm inhibited the formation of molecular clusters of heterocyclic rings, proton conduction between the heterocyclic rings was not efficient. [45,47] On the other hand, silica@PVPA/TAz exhibited low conductivity despite TAz having multiple nitrogen atoms that could act as proton-accepting sites. J. S. Lee et al have reported effect of heterocyclic compounds with acidic molecules on proton conductivity.…”
Section: Effect Of Heterocyclic Compounds For Proton Conductivitymentioning
confidence: 99%
“…Since the propyl group in 1PIm inhibited the formation of molecular clusters of heterocyclic rings, proton conduction between the heterocyclic rings was not efficient. [45,47] On the other hand, silica@PVPA/TAz exhibited low conductivity despite TAz having multiple nitrogen atoms that could act as proton-accepting sites. J. S. Lee et al have reported effect of heterocyclic compounds with acidic molecules on proton conductivity.…”
Section: Effect Of Heterocyclic Compounds For Proton Conductivitymentioning
confidence: 99%